Review: Morphofunctional and biochemical markers of stress in sea urchin life stages exposed to engineered nanoparticles. Issue 11 (30th May 2015) - Gambardella, Chiara; Ferrando, Sara; Gatti, Antonietta M.; Cataldi, Edoardo; Ramoino, Paola; Aluigi, Maria Grazia; Faimali, Marco; Diaspro, Alberto; Falugi, Carla
ABSTRACT: We describe the use of different life stages of the Mediterranean sea urchin Paracentrotus lividus for the assessment of the possible risk posed by nanoparticles (NPs) in the coastal water. A first screening for the presence of NPs in sea water may be obtained by checking their presence inside tissues of organisms taken from the wild. The ability of NPs to pass from gut to the coelomic fluid is demonstrated by accumulation in sea urchin coelomocytes; the toxicity on sperms can be measured by embryotoxicity markers after sperm exposure, whereas the transfer through the food chain can be observed by developmental anomalies in larvae fed with microalgae exposed to NPs. The most used spermiotoxicity and embryotoxicity tests are described, as well as the biochemical and histochemical analyses of cholinesterase (ChE) activities, which are used to verify toxicity parameters such as inflammation, neurotoxicity, and interference in cell‐to‐cell communication. Morphological markers of toxicity, in particular skeletal anomalies, are described and classified. In addition, NPs may impair viability of the immune cells of adult specimens. Molecular similarity between echinoderm and human immune cells is shown and discussed. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1552–1562, 2016.